2017
DOI: 10.5812/ijcm.9252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Orally-Administered Zinc in the Prevention of Chemotherapy-Induced Oral Mucositis in Patients with Acute Myeloid Leukemia

Abstract: Background: Oral mucositis is a frequent yet serious adverse event associated with chemotherapy in acute myeloid leukemia. Although a wide spectrum of drugs has been tested for prophylaxis of oral mucositis, few of them are satisfactory. There is currently substantial clinical interest in zinc (Zn) as an antioxidant and a protective agent against chemotherapy -relatednormal tissue injury. Therefore, in the present study, we investigated whether zinc prevents oral mucositis associated with chemotherapy in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 13 publications
3
27
0
10
Order By: Relevance
“…A systematic review and meta-analysis of four randomized control trials that investigated the potential effects of zinc sulfate in the prevention of radiation-induced oral mucositis among patients suffering from head and neck cancers undergoing radiotherapy, revealed that zinc sulfate may not have the benefit of prophylaxis against radiation-induced oral mucositis in these patients [43]. Similar findings were obtained in other studies focused on the potential effects of zinc sulfate in the prevention of radiation-induced oral mucositis among patients suffering from head and neck cancers undergoing radiotherapy [42,43]. In a double-blind, randomized, placebo-controlled study in which patients were given 440 mg zinc sulfate daily or placebo for 3 weeks, Mansouri and colleagues did not find any significant association between zinc sulfate and prevention, reduction in intensity and duration of oral mucositis among patients undergoing high-dose chemotherapy [44].…”
Section: Effects Of Zinc On Oral Mucositissupporting
confidence: 62%
See 2 more Smart Citations
“…A systematic review and meta-analysis of four randomized control trials that investigated the potential effects of zinc sulfate in the prevention of radiation-induced oral mucositis among patients suffering from head and neck cancers undergoing radiotherapy, revealed that zinc sulfate may not have the benefit of prophylaxis against radiation-induced oral mucositis in these patients [43]. Similar findings were obtained in other studies focused on the potential effects of zinc sulfate in the prevention of radiation-induced oral mucositis among patients suffering from head and neck cancers undergoing radiotherapy [42,43]. In a double-blind, randomized, placebo-controlled study in which patients were given 440 mg zinc sulfate daily or placebo for 3 weeks, Mansouri and colleagues did not find any significant association between zinc sulfate and prevention, reduction in intensity and duration of oral mucositis among patients undergoing high-dose chemotherapy [44].…”
Section: Effects Of Zinc On Oral Mucositissupporting
confidence: 62%
“…They found that oral zinc sulfate may not produce any clinical effects either in preventing or reducing the incidence, alleviating pain intensity, or reducing the severity of chemotherapy-induced oral mucositis [41]. In a randomized trial including leukemia patients undergoing chemotherapy to investigate whether zinc prevented chemotherapy-induced oral mucositis, supplementation with zinc sulfate for a month was not found to be associated with decreased pain intensity [42]. A systematic review and meta-analysis of four randomized control trials that investigated the potential effects of zinc sulfate in the prevention of radiation-induced oral mucositis among patients suffering from head and neck cancers undergoing radiotherapy, revealed that zinc sulfate may not have the benefit of prophylaxis against radiation-induced oral mucositis in these patients [43].…”
Section: Effects Of Zinc On Oral Mucositismentioning
confidence: 99%
See 1 more Smart Citation
“…Commencement of zinc supplementation also varied among the studies. Five of the studies had initiated zinc therapy from the first day to the last day of cancer treatment (1,5,7,9,18). Three studies had employed different time intervals of zinc treatment ranging from 10 d prior to cancer therapy till 6 wk after cessation of the therapy (2-4).…”
Section: Primary Search Strategiesmentioning
confidence: 99%
“…According to recent MASCC/ISOO clinical guidelines, the various treatment modalities include oral cryotherapy, KGF-1 (human keratinocyte growth factor), and low-level laser therapy, which may aid in prevention of oral mucositis. Two percent morphine mouthwash, transdermal fentanyl patches and 0.5% doxepin mouthwash were also recommended for alleviation of pain (9)(10)(11).…”
mentioning
confidence: 99%